1979
DOI: 10.1161/01.cir.60.3.547
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular volume from paired biplane two-dimensional echocardiography.

Abstract: To evaluate the applicability of two-dimensional echocardiography to left ventricular volume determination, 30 consecutive patients undergoing biplane left ventricular cineangiography were studied with a wide-angle (84 degrees), phased-array, two-dimensional echocardiographic system. Two echographic projections were used to obtain paired, biplane, tomographic images of the left ventricle. We used the short-axis view (from the precordial window) as an anolog of the left anterior oblique angiogram, and the long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
204
0
8

Year Published

1981
1981
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 566 publications
(217 citation statements)
references
References 8 publications
3
204
0
8
Order By: Relevance
“…13 Coronary sinus flow was calculated using the thermodilution technique, 14 MVO 2 by the Fick method, and LVEF by the Simpson biplane method. 15 Circumferential end-systolic wall stress (ESWS) was calculated using Mirsky's formula described by Douglas et al 16 …”
Section: Protocolmentioning
confidence: 99%
“…13 Coronary sinus flow was calculated using the thermodilution technique, 14 MVO 2 by the Fick method, and LVEF by the Simpson biplane method. 15 Circumferential end-systolic wall stress (ESWS) was calculated using Mirsky's formula described by Douglas et al 16 …”
Section: Protocolmentioning
confidence: 99%
“…Two factors cited by these authors to explain this discrepancy are (1) fluctuation of left ventircular volume between studies, and (2) a lack of precise endocardial definition by two-dimensional echocardiography (Carr et al, 1979;Schiller et al, 1979). The purpose of this study was to measure the contribution of these two factors in the reported underestimation of echocardiographic ventricular volume by using simultaneous contrast techniques to delineate the ventricular cavity.…”
Section: Introductionmentioning
confidence: 96%
“…When echocardiographic measurements were made at end-systole the mean echocardiographic mass for the 10 dogs was 81 ± 24 g; the correlation coefficient for the comparison of the systolic and diastolic values was .92.…”
Section: Resultsmentioning
confidence: 96%
“…IO-2 These methods are superior to M mode methods regardless of geometry'3 and many retain their accuracy in segmental disease. 10. ' I A geometrically rational method of measuring mass from two-dimensional echocardiograms is desirable because it should be less vulnerable to errors arising from the extrapolation of three-dimensional information from linear measurements and from segmental disease.…”
mentioning
confidence: 99%